T.M. Scanlon: Contractualism, Reasonableness, and Moral Intuition - Bartlett, Shawn (The Oracle, 2021)
In his article “Contractualism and Utilitarianism”, T. M. Scanlon formulates a contractualist account of moral wrongness. For Scanlon, a morally permissible principle is one that cannot be reasonably rejected within the context of an “informed, unforced general agreement.”1 Scanlon posits a hypothetical situation between agents who share a mutual recognition of each other’s value as persons. These persons are assumed to be rational individuals who are capable of formulating their own particular visions of the good; this situation is the figurative space in which a principle can be held up to the standard of reasonable rejection. Scanlon’s formulation of moral wrongness hinges on this notion of reasonableness. If we are to use it as a standard of rejection, it must be clear what Scanlon considers reasonableness to be. The goal of this paper is to clarify the meaning of reasonableness in Scanlon’s contractualism, consider how it functions within the hypothetical space of mutual recognition, and challenge its sufficiency as a standard of moral wrongness in relation to our moral intuitions